A Triple Combination of Metformin, Acetylsalicylic Acid, and Oseltamivir Phosphate Impacts Tumour Spheroid Viability and Upends Chemoresistance in Triple-Negative Breast Cancer - Sambi M; Samuel V; Qorri B; Haq S; Burov SV; Markvicheva E; Harless W; Szewczuk MR (Dove Medical Press, 2020)
Manpreet Sambi,1 Vanessa Samuel,1,2 Bessi Qorri,1 Sabah Haq,1,3 Sergey V Burov,4 Elena Markvicheva,5 William Harless,6 Myron R Szewczuk1 1Department of Biomedical and Molecular Sciences, Queen’s University, Kingston, ON, Canada; 2Faculty of Medicine, University of British Columbia, Vancouver, BC, Canada; 3Department of Pathology and Molecular Medicine, McMaster University, Hamilton, ON, Canada; 4Laboratory of Novel Peptide Therapeutics, Cytomed J.S.Co., St. Petersburg, Russia; 5Biomedical Materials Laboratory, Shemyakin-Ovchinnikov Institute of Bioorganic Chemistry, Russian Academy of Sciences, Moscow, Russia; 6Encyt Technologies, Inc., Membertou, Nova Scotia, CanadaCorrespondence: Myron R SzewczukDepartment of Biomedical and Molecular Sciences, Queen’s University, Kingston, ON K7L3N6, CanadaTel +1 613 533 2457Fax +1 613 533 6796Email szewczuk@queensu.caIntroduction: Targeted multimodal approaches need to be strategically developed to control tumour growth and prevent metastatic burden successfully. Breast cancer presents a unique clinical problem because of the variety of cellular subtypes that arise. The tumour stage and cellular subtypes often dictate the appropriate clinical treatment regimen. Also, the development of chemoresistance is a common clinical challenge with breast cancer. Higher doses and additional drug agents can produce additional adverse effects leading to a more aggressive malignancy. Acetylsalicylic acid (ASA), metformin (Met), and oseltamivir phosphate (OP) were investigated for their efficacy to sensitize MDA-MB-231 triple-negative breast cancer and its tamoxifen (Tmx) resistant variant (MDA-MB-231-TmxR) together in combination with Tmx treatment.Methods: Microscopic imaging, the formation of 3D multicellular tumour spheroids, immunocytochemistry, flow cytometry, Annexin V Assay, Caspase 3/7 Apoptosis Assay, tube formation assay and analysis, and WST-1 cell viability assay evaluated the formation of MCTS, morphologic changes, cell viability, apoptosis activity and the expression levels of ALDH1A1, CD44 and CD24 on the cell surface, MDA-MB231 triple-negative breast cancer, tamoxifen (Tmx) resistant variant (MDA-MB-231-TmxR).Results: The results using a triple combination of ASA, Met and OP on MDA-MB-231 and MDA-MB-231-TmxR cells and their matrix-free 3D multicellular tumour spheroids (MCTS) formed by using the cyclic Arg-Gly-Asp-D-Phe-Lys peptide modified with 4-carboxybutyl-triphenylphosphonium bromide (cyclo-RGDfK(TPP)) peptide method demonstrate a consistent and significant decrease in cell and tumour spheroid viability and volume with increased apoptotic activity, and increased sensitivity to Tmx therapy. Tmx treatment of MDA-MB-231 cells in combination with ASA, Met and OP markedly reduced the CD44/CD24 ratio by 6.5-fold compared to the untreated control group. Tmx treatment of MDA-MB-231-TmxR cells in combination with ASA, Met and OP markedly reduced the ALDH1A1 by 134-fold compared to the same treatment for the parental cell line. Also, the triple combination treatment of ASA, Met, and OP inhibited vasculogenic endothelial cell tube formation and induced endothelial cell apoptosis.Conclusion: For the first time, the findings demonstrate that repurposing ASA, Met, and OP provides a novel and promising targeted multimodal approach in the treatment of triple-negative breast cancer and its chemoresistant variant.Keywords: MDA-MB-231, MDA-MB-231-TmxR, human umbilical vein endothelial cell lines, multicellular tumour spheroids, MCTS, endothelial cell tube formation, apoptosis